Spontaneously Conceived Pregnancy after 40: Influence of Age and Obesity on Outcome - Barton, John R.; Sibai, Amanda J.; Istwan, Niki B.; Rhea, Debbie J.; Desch, Cheryl N.; Sibai, Baha M. (American Journal of Perinatology, 2014)
Objective The aim of the study was to examine pregnancy outcomes of healthy nulliparous women aged ≥ 40 years at delivery.Study Design The study included 53,480 nulliparous women aged 20 to 29 or ≥ 40 years delivering singleton infants, enrolled in a pregnancy risk assessment program between July 1, 2006, and August 1, 2011. Women reporting medical disorders, tobacco use, or conception with assistive reproductive technology were excluded. Data were grouped by body mass (obese or nonobese) and age (20–29 or ≥ 40 years). Pregnancy outcomes were compared within each body mass group for women aged 20 to 29 years versus ≥ 40 years and between obese and nonobese women aged ≥ 40 years.Results Within each body mass group, nulliparous women aged ≥ 40 years delivered at a significantly lower gestational age and had a greater incidence of cesarean delivery, gestational diabetes, preterm birth, and both low and very low birth weight infants, compared with controls aged 20 to 29 years. For women aged ≥ 40 years, obesity was associated with higher rates of adverse pregnancy outcomes.Conclusion In healthy women, both advanced maternal age and obesity negatively influence pregnancy outcomes. Women who delay pregnancy until age 40+ years may modify their risk for cesarean section, preterm birth, and low-birth-weight infants by reducing their weight to nonobese levels before conception.
Keywords: advanced maternal age; obesity; pregnancy outcomes; risk assessment